Investigating the relationship between transformational leadership style and organizational identity of faculty members in the state universities of West Azerbaijan Province, Iran - Hesar, Ali Pourmahmoud; Abbaszadeh, Mir Mohammad Seyed; Ghaleei, Alireza; Ghalavandi, Hassan (Serbian Journal of Management, 2019)
The aim of this research was to investigate the relationship between transformational leadership style and organizational identity of faculty members in the state universities of West Azerbaijan Province, Iran. This research was a descriptive and correlational study. The statistical population of the research included all faculty members of these universities whose number was 765 at the time the research was conducted. Using Morgan table and stratified random sampling method, 256 persons were selected as the statistical sample of the research. 300 questionnaires were distributed among which 283 were returned, the final data analysis was conducted for 283 persons using SPSS and LISREL software. Standard multifactor leadership questionnaire (MLQ) and Cheney's organizational identity questionnaire (1982) were used to collect data regarding transformational leadership and organizational identity, respectively. The reliability of the questionnaires was calculated to be 0.96 and 0.85, respectively, using cronbach's alpha coefficient. Hypothesis and assumed relationships between variables in the proposed theoretical model were investigated using regression analysis and structural equation model. The results obtained from this research showed that there was a positive and meaningful relationship between transformational leadership style and its variables and organizational identity of faculty members in the state universities of West Azerbaijan Province, Iran (p